The last anniversary [videorecording (DVD)] - Strauss, Samantha (Sundance Now, 2025)
"Sophie Honeywell finds herself drawn into a complex web of family secrets after inheriting a house on a remote island famous for the disappearance of a young couples decades ago. After the unwelcome reception she receives, she begins to investigate the mysteries of the island and finds herself drawn into the long-held family secrets spanning three generations of women, uncovering far more than ever expected"--